Sensitivity of elite tennis players to string tension - Bower, R.; Cross, R. (2002)
Most experienced tennis players report that a small change in string tension can make a significant difference to the feel or performance of their racket. In a previous study, we set out to determine whether this effect is real or perceived, by testing the level of discrimination in a sample of 41 experienced male and female tennis players. We found that 73% of the players could not detect a difference of 5 kg (11 lb.) in string tension. Neither the sound of the impact, nor the feel or performance of the racquet were sufficiently different for most players to notice even large changes in string tension. None of the players tested in that study was of elite or professional standard. We have since undertaken a similar study with elite male players who were competing professionally in a satellite tournament in Sydney. These players could detect slightly smaller differences in tension, but 61% were unable to perceive a difference in tension of 5 kg. Professional players appear to be especially sensitive to changes in string tension since most of them have their rackets restrung prior to every match in a tournament. This is not just a precaution against breaking a string, since professional players usually bring up to six identical rackets onto the court. Elite players appear to notice a difference in string performance even after playing a few sets with a newly-strung racket. Most commonly, elite players describe new strings as feeling 'crisp' or 'lively' and strings used for four or five sets as feeling 'dead'. Recreational players are less likely to be as sensitive to string tension. It is generally accepted that a racket should be strung at low tension for increased power and at high tension for better control. The explanation for the increase in power is that the ball deforms less when it impacts on softer strings, and will rebound at higher speed due to the decreased energy loss in the ball. The strings themselves store and return energy much more efficiently than the ball. At higher tensions, the impact duration is decreased, with the result that the racket rotates through a smaller angle during impact, leading to improved control in both the horizontal and vertical directions. While both of these explanations are valid, the inference is that the increased power or control is substantial. In fact, recent estimates indicate that the increase in power or control for e.g. a 20% change in tension is typically only about 1%. Consequently, the question arises as to whether this is significant or even detectable. It is relatively easy to detect a small change in string tension by listening to the sound made by the strings when they vibrate. In this respect, the strings of a racket behave like the strings of a guitar or piano. In a racket or in a musical instrument, the vibration frequency of the strings increases in proportion to the square root of the string tension. Most people can easily detect a frequency change of 6%, which is the difference in frequency of adjacent notes on a piano. A 6% change in string frequency corresponds to a 12% change in string tension. Consequently, if a racket is strung at e.g. 28 kg, it should be easy to detect a change in tension of about 3 kg simply by listening to the string vibrations. However, many tennis players, including professionals, dislike the 'ping' sound coming from the strings of their racket and prefer to use a string dampener that turns the long 'ping' into a short 'thud'. The pitch of a 'thud' is more difficult to detect. Consequently, all tests were made with a string dampener installed, since the primary objective was to determine whether players could detect changes in string tension without the obvious cue coming from the sound of the strings vibrating. Four identical racquets were strung at different tensions, and players were asked to compare the tensions in two racquets after hitting four forehands with each racquet. This was repeated using several different pairs of racquets to determine the discrimination level of each player.